A Mixed-Methods Evaluation of Usability and Acceptability of Web-Based Relapse Prevention and Self-Monitoring Program: Secondary Analysis of a Pilot Randomized Controlled Trial - Takano, Ayumi; Matsumoto, Toshihiko (Frontiers in Psychiatry, 2021)
This secondary analysis of a pilot randomized controlled trial assessed the usability and acceptability of a web-based relapse prevention and self-monitoring program, which was newly developed for Japanese drug users. We analyzed quantitative and qualitative data using a mixed-method approach among 43 study participants. We assessed the usability of the programs using the Web Usability Scale (WUS) and satisfaction and acceptance using the Client Satisfaction Questionnaire 8-item version (CSQ-8). We also collected qualitative feedback using semi-structured open-ended questions. The results of WUS indicated that the usability of the programs was sufficient. According to the CSQ-8 results, the self-monitoring program had less satisfaction, while the web-based relapse prevention program met satisfaction. Some possible improvements for a future version of the web-based programs were suggested based on participants’ feedback.